Pengembangan LKPD Case-Based Learning Terintegrasi Pendidikan Karakter pada Materi SPLDV - Rika Handayani; Maria Naimnule (J-PiMat : Jurnal Pendidikan Matematika, 2026)
This study aims to develop a Case-Based Learning-based LKPD integrated with character education on SPLDV material. This study uses the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 31 ninth-grade students of SMPN Mubeli who were selected by purposive sampling. Product validity was assessed by material experts, media experts, and character education experts. The practicality of the LKPD was measured through teacher and student response questionnaires, while effectiveness was analyzed based on the results of the post-test and student character questionnaires. The results showed that the developed LKPD had a very high level of validity with an average score of 90%. The practicality level of the LKPD was in the very practical category with an average of 91.3%. Furthermore, the Student Worksheet (LKPD) proved effective in improving student learning outcomes, with an average post-test score of 81.71 and classical completion reaching 100%. The character questionnaire results also showed improvements in critical reasoning, honesty, and responsibility, all within the good category. Thus, the Case-Based Learning-based LKPD, integrated with character education based on the local context of NTT, is declared valid, practical, and effective for use in SPLDV learning.Keyword: Student Worksheet, Case Based Learning, Character Education, SPLDV